2023
DOI: 10.3390/app13116507
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Agriculture through the Enhancement of Microbial Biocontrol Agents: Current Challenges and New Perspectives

Arun Gokul,
Jabulani Mabaso,
Nontuthuko Henema
et al.

Abstract: The future of pesticide usage in agriculture is uncertain due to its unsustainability, adverse environmental impacts, and its association in enhanced phytopathogen resistance. Hence, this situation urges the development of new sustainable practices in agriculture. A promising approach involves endophytes, which are non-pathogenic microorganisms inhabiting the interior parts of plants. However, due to the vast diversity and complexity of plant microbiomes, a major gap has formed with regards to endophytic resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Therefore, appropriate knowledge, accessibility, and regulation of endophyte application should lead to expanded utilization across various agricultural sectors promoting crop yield and protecting the environment. However, useful the applications are, the utilization of endophytes in agricultural production comes with its challenges [11,128]. They include inadequate understanding of the ecological roles of endophytes, insufficient commercial microbial inoculant stocks [129], and regulatory barriers [130].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, appropriate knowledge, accessibility, and regulation of endophyte application should lead to expanded utilization across various agricultural sectors promoting crop yield and protecting the environment. However, useful the applications are, the utilization of endophytes in agricultural production comes with its challenges [11,128]. They include inadequate understanding of the ecological roles of endophytes, insufficient commercial microbial inoculant stocks [129], and regulatory barriers [130].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…Therefore, interdisciplinary efforts are imperative in advancing the endophyte research [131]. "Researchers studying endophytes face difficulty in isolating underrepresented endophytes due to the vast diversity of plant microbiomes [ 132], a tendency to focus on well-known models in plant-fungal-stress combinations rather than exploring less studied factors [133], and the need for novel approaches in genotyping and phenotyping to consider the plantendophyte holobiont for breeding programs" [134]. Additionally, one of the conditions for the development of breeding endophytes is the necessity for a new approach in genotyping and phenotyping that takes into account the plant-endophyte holobiont [135].…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising directions for the future of omic-based biological control strategies lie in harnessing the vast potential of these advanced technologies to further enhance and optimize the efficacy of BCAs in agriculture and pest management. Integrating genomics, transcriptomics, proteomics, and metabolomics approaches can provide a comprehensive understanding of the complex interactions between BCAs and their target pests or pathogens, leading to the discovery of novel bioactive compounds and mechanisms involved in biocontrol [100]. Omic tools can facilitate the identification of key genes and pathways involved in the production of biocontrol-related secondary metabolites, such as antibiotics and enzymes, which are crucial for inhibiting pathogen growth [100].…”
Section: Elucidation Of Plant and Microorganism Interactions For The ...mentioning
confidence: 99%
“…Integrating genomics, transcriptomics, proteomics, and metabolomics approaches can provide a comprehensive understanding of the complex interactions between BCAs and their target pests or pathogens, leading to the discovery of novel bioactive compounds and mechanisms involved in biocontrol [100]. Omic tools can facilitate the identification of key genes and pathways involved in the production of biocontrol-related secondary metabolites, such as antibiotics and enzymes, which are crucial for inhibiting pathogen growth [100]. For example, the research carried out by Villa Rodríguez et al [67], integrating genomic and metabolomic results from the effect of Bacillus cabrialesii TE3 T on Bipolaris Sorokiniana TPQ3, revealed that strain TE3 T contains the biosynthetic potential to produce wide spectrum antifungal and antibacterial metabolites, and determined that a lipopeptide complex of surfactin and fengycin homologs was responsible for antifungal activity exhibited by B. cabrialesii TE3 T against the studied phytopathogen.…”
Section: Elucidation Of Plant and Microorganism Interactions For The ...mentioning
confidence: 99%